Pengembangan Instrumen Kompetensi Profesional Guru Matematika Terintegrasi Nilai-Nilai Pendidikan Islam Berbasis Abad 21 - Giantara, Febri; Hitami, Munzir; Risnawati, Risnawati (UIR Press, 2023)
The 21st century requires teachers to be able to have professional competence and also master IT. Mastering IT without being accompanied by the values of Islamic Religious Education will result in the birth of a generation that is intellectual but far from religious teachings. This will certainly cause a lot of damage on Earth later. To overcome this, it is necessary to develop an instrument that is able to measure the professional competence of high school mathematics teachers integrated with Islamic Religious Education values based on the 21st century. This ADDIE model is combined with the Andromeda Spiral Integration model. The sample of this study was 210 students at public high schools in Tapung District, Kampar Regency. The data analysis used was using EFA and CFA analysis which was analyzed with the SPSS 21 application. The development results showed that the instrument was successfully developed and met the validity, reliability and practicality for the development of an instrument. This study also succeeded in finding an integration model for the instrument developed which was named Spiral Andromeda Factor Analysis (SAAF).